Population-level productivity-adjusted life years lost in individuals with type 2 diabetes in Hong Kong: a life table modelling studyResearch in context - Hongjiang Wu; Haobin Zhou; Chuiguo Huang; Aimin Yang; Eric S.H. Lau; Xinge Zhang; Baoqi Fan; Ronald C.W. Ma; Alice P.S. Kong; Elaine Chow; Wing-Yee So; Juliana N.M. Lui; et al. (The Lancet Regional Health. Western Pacific)
Summary: Background: Type 2 diabetes has become increasingly prevalent in young populations who are in their prime working years. We estimated the population-level productivity-adjusted life years (PALYs) lost in the working-age population with type 2 diabetes in Hong Kong. Methods: We constructed life tables for individuals aged 20–64 years with type 2 diabetes, with simulated follow-up until retirement at 65 years. We then re-simulated the life tables for the same cohort with the hypothetical assumption that they did not have diabetes, adjusting for differences in mortality rates, labour force participation rates, and productivity. We calculated diabetes-related PALYs lost and assumed the cost of each PALY to be equivalent to the annual gross domestic product (GDP) per worker. Findings: In 2019, 6.3% (n = 139,610) of men and 4.2% of women (n = 117,670) of working age had diagnosed type 2 diabetes in Hong Kong. Over their working lifetime, diabetes was associated with a 17.0% (95% CIs: 16.9%, 17.1%) reduction in PALYs in men and 27.8% (95% CIs: 27.6%, 28.0%) in women, equivalent to 1.0 (95% CIs: 1.0, 1.0) and 1.1 (95% CIs: 1.1, 1.1) PALYs lost per man and woman, respectively. Younger individuals with diabetes experienced greater per-person PALYs lost than older individuals. Men and women aged 20–24 years lost 3.9 (95% CIs: 3.9, 3.9) and 5.0 (95% CIs: 5.0, 5.0) PALYs per person due to diabetes, compared to 0.3 (95% CIs: 0.3, 0.3) PALYs in both sexes aged 60–64 years. The total PALYs lost resulted in a GDP loss of USD 15.3 (95% CIs: 15.2, 15.4) billion in men and USD 14.5 (95% CIs: 14.4, 14.6) billion in women. Interpretation: Type 2 diabetes was associated with substantial reductions in PALYs and indirect economic costs in Hong Kong, with disproportionate impacts on women and younger populations. Targeted interventions are needed to address these disparities and mitigate the dual burden of health and economic consequences of diabetes. Funding: Direct Grant for Research from The Chinese University of Hong Kong.